The need to apply innovative education and digital technologies to higher education - Nematova Mavsuma Ulugbek kizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
Although it existed in a few different forms earlier, digital education is essentially a modern invention. It is the digitalization of a segment of the educational system. This article attempts to offer insightful thoughts on the future potential and difficulties of information and communication technology (ICT) and digital education as they relate to adopting the most recent technological advancements in the digital era and extensive online open courses. With the development of internet technology, we have observed a significant shift in how we communicate and collaborate among academics. The digital revolution encouraged unrestricted access to information on a global scale.